Converse Lyapunov–Krasovskii theorems for uncertain retarded differential equations. (December 2015) - Haidar, Ihab; Mason, Paolo; Sigalotti, Mario
Abstract: In this article we give a collection of converse Lyapunov–Krasovskii theorems for uncertain retarded differential equations. We show that the existence of a weakly-degenerate Lyapunov–Krasovskii functional is a necessary and sufficient condition for the global exponential stability of linear retarded functional differential equations. This is carried out using a switched system representation approach.